Arterial hypertension and periodontitis association. - López-Ilisástigui, Alina (2017)
Objectives: In to population to determine the presence of arterial hypertension and to relate it with the presence and periodontitis severity, age, color of the skin and nutritional state. Methods: Carries out a descriptive traverse study in 149 mature individuals and that they accepted in a voluntary way to participate in the investigation. The studied variables were presence of arterial hypertension, age, color of the skin, nutritional state and he/she witnesses and periodontitis severity. Arterial Results: hypertension met with more frequency in individuals of black skin and of corporal bigger weight, nose found differences as for the age, in the same ones it was more frequent and severity the periodontitis chronicle. Conclusions: The presence of arterial hypertension was similar to that of the Cuban population, being related with periodontitis chronicle presence and severity. The age 20-29 years, the color black of the skin and corporal bigger weight, were more frequently.